Memory-relevant nap sleep physiology in healthy and pathological aging - Ladenbauer, Julia; Ladenbauer, Josef; Külzow, Nadine; Flöel, Agnes (Sleep (New York, N.Y.), 2021)
Abstract Study Objectives Aging is associated with detrimental changes in sleep physiology, a process accelerated in Alzheimer’s disease. Fine-tuned temporal interactions of non-rapid eye movement slow oscillations and spindles were shown to be particularly important for memory consolidation, and to deteriorate in healthy older adults. Whether this oscillatory interaction further decline in early stages of Alzheimer’s disease such as mild cognitive impairment has not been investigated to date, but may have important therapeutic implications. Methods Here, we assessed differences in sleep architecture and memory-relevant slow oscillation, sleep spindles and their functional coupling during a 90-min nap between healthy young and older adults, and in older patients with mild cognitive impairment. Furthermore, associations of nap-sleep characteristics with sleep-dependent memory performance change were evaluated. Results We found significant differences between young and older healthy adults, and between young adults and patients with mild cognitive impairment, but not between healthy older adults and patients for several sleep metrics, including slow oscillation-spindle coupling. Moreover, sleep-dependent retention of verbal memories was significantly higher in young healthy adults versus older adults with and without mild cognitive impairment, but no difference between the two older groups was observed. Associations with sleep metrics were only found for pre-nap memory performances. Conclusions In conclusion, our results indicate changes in nap sleep physiology and sleep-related memory consolidation in older adults with and without mild cognitive impairment. Thus, interventions targeted at improving sleep physiology may help to reduce memory decline in both groups, but our study does not indicate additional benefits for patients with mild cognitive impairment. Clinical Trail Registration Effects of Brain Stimulation During Daytime Nap on Memory Consolidation in Younger, Healthy Subjects: https://clinicaltrials.gov/ct2/show/NCT01840865; NCT01840865. Effects of Brain Stimulation During a Daytime Nap on Memory Consolidation in Older Adults; https://clinicaltrials.gov/ct2/show/study/NCT01840839?term=01840839&draw=2&rank=1; NCT01840839. Effects of Brain Stimulation During a Daytime Nap on Memory Consolidation in Patients With Mild Cognitive Impairment; https://clinicaltrials.gov/ct2/show/NCT01782365?term=01782365&draw=2&rank=1; NCT01782365.